Filogenia e revisão taxonômica de Davilla Vand. (dilleniaceae) - Claudio Nicolete de Fraga (2012)
Dilleniaceae is a pantropical family with about 500 species, grouped in 10 genera, mostly restricted to one region of the earth (mainly neotropical or paleotropical) except for Tetracera, that is pantropical. Four subfamilies were established within it based on phylogenetic analysis using molecular data. In this proposition, Tetracera remain as a sister group to all other subfamilies, and is the only genus of the pantropical Delimoideae. The Doliocarpoideae are restricted to Neotropics, and emerge as a sister group to the other subfamilies: Hibbertioideae, restricted to Oceania, and Dillenioideae, distributed in Asia and part of the Oceania. Species from the Neotropics are arranged in six genera: Tetracera (Delimoideae), Curatella, Davilla, Doliocarpus, Neodillenia and Pinzona(Doliocarpoideae). The main goal of this work was to clarify the relationships among the subfamilies and the tropical genera, in a phylogenetic conspectus, as well as to test the monophyly of the genus Davilla using both molecular and morphologic data. A revision of Davilla is also presented and the relationships between its sections are hypothesized. The phylogeny agrees with past propositions, showing Dilleniaceae as monophyletic, as well as its subfamilies and the genus Davilla, all well supported. For the sections of Davilla established in past treatments only Davilla sect. Davilla emerged as monophyletic, and Davilla sect. Homalochlena as paraphyletic. Our results show four main clades within Davilla, but only two well supported and with consistent morphological synapomorphies. A satisfactory proposition ispresented and regards a new circumscription of D. sect. Homalochlaena and the description of two new sections: Davilla sect. Complanata and Davilla sect. Dryadica. Of the 78 names cited to Davilla, 34 are lectotypified here, two of these being epitypified, four neotypes are proposed and six names are excluded of the genus. Twenty eight species are recognized to Davilla, seven new species were discovered, four of these have were published and three are presented here as new.